Fecal Microbial and Metabolomic Change during treatment course for depression: An Observational Study. (August 2021) - Kurokawa, Shunya; Tomizawa, Yoshihiro; Miyaho, Katsuma; Ishii, Daiki; Takamiya, Akihiro; Ishii, Chiharu; Sanada, Kenji; Fukuda, Shinji; Mimura, Masaru; Kishimoto, Taishiro
Abstract: Background: There is growing evidence regarding the connection between alterations in gut microbiota and their metabolites in patients with depressive disorders, suggesting a potential role in pathophysiology. Our study aimed to investigate the relationship between microbial, metabolomic features and the course of treatment for depression in a real-world clinical setting. Methods: Patients diagnosed with depressive disorders were recruited, and their stool was collected at three time points during their depression treatments. Patients were divided into three groups: non-responders, responders, and stable remitters. Gut microbiomes were analyzed using 16S rRNA gene sequencing, and gut metabolomes were analyzed by a mass spectrometry approach. Microbiomes/metabolomes were compared between groups cross-sectionally and longitudinally. Results: A total of 33 patients were recruited and divided into non-responders (n = 16), responders (n = 11), and stable remitters (n = 6). Non-responders presented lower alpha diversity in the Phylogenic Diversity index compared to responders during the treatment course (p = 0.003). Non-responders presented increased estimated glutamate synthesis functions by the microbiota compared to responders and stable remitters (p = 0.035). There were no specific microbiota or metabolome that differentiated the three groups. Limitations: Small sample size with no healthy controls. Conclusions: Our results indicate that both cross-sectional microbial features and longitudinal microbial transitions are different depending on the treatment course of depression. Controlled studies, as well as animal studies, are needed in the future to elucidate the causal relationship between microbiota and depression. Highlights: Depression treatment non-responders presented lower alpha diversity in the Phylogenetic diversity whole tree index compared to responders during treatment. Treatment non-responders presented an increased estimated function of glutamate synthesis by the microbiome compared to responders and stable remitters. Larger controlled studies are needed to elucidate the relationship of the microbiome and mood disorders.